Effects of bacterial cell-free supernatant on nutritional parameters of Apis Mellifera and their toxicity against Varroa Destructor - de Piano, Fiorella Giselle (2020)
Apis mellifera L. is an essential pollinator that is currently being affected by several stressors that disturb their ecological function and produce colony losses. Colonies are being seriously affected by the ectoparasitic mite Varroa destructor. The relationship between stressors and bee symbionts is being studied in order to enhance bee health. The goal of this study was to evaluate the effect of cell-free supernatants (CFSs) produced by Lactobacillus johnsonii AJ5, Enterococcus faecium SM21 and Bacillus subtilis subsp. subtilis Mori2 on A. mellifera nutritional parameters and their toxicity against V. destructor. Toxicity and survival bioassays were conducted on adult bees with different concentrations of CFSs. Nutritional parameters such as soluble proteins and fat bodies in abdomens were measured. Varroa destructor toxicity was analyzed by a contact exposure method and via bee hemolymph. At low concentrations, two of CFSs tends to enhance bee survival. Remarkably fat bodies maintained their levels with all CFS concentrations in the abdomens, and soluble protein increased at a high concentration of two CFSs. Toxicity against V. destructor was observed only via hemolymph, and results were in agreement with the treatment that produced an increase in bee proteins. Finally, CFS produced by L. johnsonii AJ5 could be a promising natural alternative for strengthening bee health.